Fast identification of the conduction-type of nanomaterials by field emission technique. Issue 1 (December 2017) - Yang, Xun; Gan, Haibo; Tian, Yan; Peng, Luxi; Xu, Ningsheng; Chen, Jun; Chen, Huanjun; Deng, Shaozhi; Liang, Shi-Dong; Liu, Fei
Abstract There are more or less dopants or defects existing in nanomaterials, so they usually have different conduct-types even for the same substrate. Therefore, fast identification of the conduction-type of nanomaterials is very essential for their practical application in functional nanodevices. Here we use the field emission (FE) technique to research nanomaterials and establish a generalized Schottky-Nordheim (SN) model, in which an important parameter λ (the image potential factor) is first introduced to describe the effective image potential. By regarding λ as the criterion, their energy-band structure can be identified: (a) λ = 1: metal; (b) 0.5 < λ < 1: n-type semiconductor; (c) 0 < λ < 0.5: p-type semiconductor. Moreover, this method can be utilized to qualitatively evaluate the doping-degree for a given semiconductor. We test numerically and experimentally a group of nanomaterial emitters and all results agree with our theoretical results very well, which suggests that our method based on FE measurements should be an ideal and powerful tool to fast ascertain the conduction-type of nanomaterials.